Public Health Professional (PHP.): Proactive Roles in Advancing Community Health through One Health Innovation - Namjud, Nuttaphat; Suksawang, Chaninpong; Somporn, Kanokporn (Journal of Public Health and Innovation, 2026)
Public health professional (PHP.) serve as a vital force in driving community health systems amidst a global context characterized by increasingly complex health challenges, ranging from the emergence of infectious diseases and environmental crises to shifting health behaviors in the digital age. Consequently, the implementation of the One Health approach has become a fundamental key to interconnecting human, animal, and environmental health. By integrating multidisciplinary collaboration to monitor and address systemic issues effectively, this approach fosters sustainable health security and mitigates biological threats that may impact both humanity and the global ecosystem. This article aims to describe the proactive roles of public health professionals in advancing communities toward proactive health through the integration of One Health innovation. Synthesis of four fundamental principles: 1) Public Health Professional Identity. 2) Implementing proactive health approaches through community participation processes. 3) Integrating the One Health concept to holistically connect human, animal, and environmental health and 4) The application of health innovation to strengthen community health systems through the holistic integration of human, animal, and environmental health. Based on the synthesis of conceptual perspectives and empirical evidence, the findings indicate that public health professionals play significant roles as innovation change agents by applying digital technologies and social innovations at the local level to improve service delivery and increase the efficiency of community health systems. In addition, they contribute substantially to driving health policy implementation across all sectors in accordance with the Health in All Policies approach of the Ministry of Public Health, which promotes interconnected, integrated, and responsive public health operations aligned with the country’s Sustainable Development Goals. The integration of health innovation with the One Health approach therefore represents an important strategy for strengthening resilient, equitable, and sustainable healthy communities in the future. PHP. serve as central driving forces in mobilizing multisectoral collaboration to advance the country toward the full achievement of Sustainable Development Goal 3 (Good Health and Well-being) in the future.